Generations and New Technologies between Utopia and Dystopia - Monti, Luciano (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The impact of new technologies on the economy, on democracy, on the individual and on the environment, often diametrically opposed feelings, from the enthusiasm for disruptive technologies, to the denunciation of the ethical implications of genome editing. The XIX and XX centuries authors of literary dystopias are the first interpreters of the great fears of modernity and the unwanted effects of new technologies. This paper proposes a cross-reading of scientific and literary contributions on this theme to show that technology is an independent variable capable on one hand of restoring the well-being that the large number of people have lost; on the other hand of representing a factor of social exclusion. To define a Policy that accompanies the society and the economy to face new technologies, we need a metric and the identification of some multidimensional indicators that can be used to determine realistic targets to be achieved in the coming future. The composite indicator on innovation, together with that linked to sustainable growth, represent the main tools for the evaluation platform proposed in this paper. Keywords: New Technologies, Generational Divide Index, Utopa, Dystopia, Future.